Elevated Plasma Surfactant Protein D (SP‐D) Levels and a Direct Correlation with Anti‐severe Acute Respiratory Syndrome Coronavirus‐specific IgG Antibody in SARS Patients - Wu, Y. P. (Scand J Immunol, 2009)
Pulmonary SP‐D is a defence lectin promoting clearance of viral infections. SP‐D is recognized to bind the S protein of SARS‐CoV and enhance phagocytosis. Moreover, systemic SP‐D is widely used as a biomarker of alveolar integrity. We investigated the relation between plasma SP‐D, SARS‐type pneumonia and the SARS‐specific IgG response. Sixteen patients with SARS, 19 patients with community‐acquired pneumonia (CAP) (Streptococcus pneumonia) and 16 healthy control subjects were enrolled in the study. Plasma SP‐D and anti‐SARS‐CoV N protein IgG were measured using ELISA. SP‐D was significantly elevated in SARS‐type pneumonia [median (95% CI), 453 (379–963) ng/ml versus controls 218 (160–362) ng/ml, P < 0.05] like in patients with CAP. SP‐D significantly correlated with anti‐SARS‐CoV N protein IgG (r (2) = 0.5995, P = 0.02). The possible re‐emergence of SARS or SARS‐like infections suggests a need for minimal traumatic techniques for following the alveolar compartment, e.g. during testing of antivirals. We suggest that monitoring systemic SP‐D may be useful in monitoring the alveolar integrity in SARS‐type pneumonia. The significant correlation between plasma SP‐D and anti‐SARS‐CoV‐specific antibodies support the role for SP‐D in interlinking innate and adaptive immune pathways.